Profiles of instrumental, emotional, and informational support in Chinese breast cancer patients undergoing chemotherapy: a latent class analysis - Tingting Cai; Qingmei Huang; Changrong Yuan (BMC, 2021)
Abstract Background To date, few studies have assessed social relationships in patients with breast cancer during their chemotherapy process. This study aimed to explore profiles of instrumental, emotional, and informational support in Chinese breast cancer patients undergoing chemotherapy. Methods In a cross-sectional study performed between September 2018 and September 2020 in China, 638 patients with breast cancer completed demographic information questionnaires, the PROMIS-Social Relationships Short Forms, the PROMIS-Anxiety Short Form, and the PROMIS-Depression Short Form. Analysis of variance and chi-square tests were performed to examine between-group differences in demographic characteristics, anxiety, and depression outcomes across the identified latent classes. Multinomial logistic regression was performed to identify the correlation of significant variables among the identified classes. Results Three profiles of social relationships were identified: Class 1-low social relationships group (14.3%), Class 2-high instrumental support, medium emotional and informational support group (24.6%), and Class 3-high social relationships group (61.1%). The findings revealed the heterogeneity of instrumental, emotional, and informational support in Chinese breast cancer patients undergoing chemotherapy, which was significantly correlated with educational background, monthly family income, health insurance, and employment status. Additionally, patients with low instrumental, emotional, and informational support were more likely to report high levels of anxiety and depression. Conclusions When conducting interventions to promote social relationships during the chemotherapy process, healthcare providers should consider the sociodemographic characteristics, anxiety levels, and depression symptoms of patients with breast cancer and identify high-risk patients for tailored interventions.